The mediating role of leader's emotional intelligence in the relationship between perceived leadership styles and employee engagement in Palestine - Milhem, Marwan M. A.; Universiti Sultan Zainal Abidin . Faculty of Business and Management (2020)
Employee engagement has been at the center of attention for human resource personnel and researchers, and it is claimed to be a key driver of organizational business Success. In the Middle East and North Africa, it was found that only 10% of employees are engaged in their jobs, while in Palestine only 11 % of employees are engaged in work. Many studies reported that Palestinian employees have been suffering from a lack of managerial leadership skills in order to lead employees in the wo11lqllace. Around 90% of Palestinian managers encourage employees to complete their work by u ing financial rewards; whereas, non-financial motivation and leader's emotional intelligence are sparingly used to reward them. This study aims to investigate the mediating effects of emotional intelligence in the relationship between perceived leadership styles and employee engagement in Palestine. The study employed a quantitative metho u'ng a descriptive research design. The population in this study comprised 5281 full-time employees in the Information and Communication Technology (lCT) sector in Palestine. A sample of 328 employees was selected using a simple random sampling method. A set of self-administered questionnaire survey was established based on the adoption and adaptation of the theories and previous studies as the instrument for data collection; and validated using expert review, pre-testing. The pilot study data was analyzed using Exploratory Factor Analysis (EF A). This study employed the Structural Equation Modeling (SEM) in IBM SPSS AMOS 21.0 to test the hypotheses. The study found that the transformational leadership style has a significant direct effect on employee engagement and the leader's emotional intelligence in the context of Palestine. Transactional leadership style, on the other hand, has no significant direct effect on employee engagement, but it has a significant direct effect on leaders' emotional intelligence. The results also showed that leaders' emotional intelligence has a significant direct effect on employee engagement. The effect of transformational leadership on employee engagement was found to be partially mediated by leaders' emotional intelligence at work. There is a large effect size of leader's emotional intelligence by the transformational leadership on employee engagement. On the other hand, the results of mediation analysis showed that leaders' emotional intelligence fully mediated the relationship between transactional leadership on employee engagement with a small effect size. In conclusion, leadership styles and leaders' emotional intelligence were found to playa very important role in engaging employees in the workplace. This study is significant in terms of addressing the gap found in the previous literature, which that will contribute to the body of knowledge and add to the industry in the context of Palestine and the Middle Eastern Region.
1. Introduction -- 2. Literature review -- 3. Conceptual framework & hypotheses development -- 4. Research methodology -- 5. Data analysis, finding and discussion -- 6. Conclusions & recommendations
Thesis (Degree of Doctor of Philosophy) - Universiti Sultan Zainal Abidin, 2020
Includes bibliographical references (leaves 230-250)
Keywords: Universiti Sultan Zainal Abidin -- Dissertations; Universiti Sultan Zainal Abidin -- Faculty of Business and Management -- Dissertations; Dissertations, Academic; Emotional intelligence; Emotional intelligence -- Palestine; Employee motivation; Leadership -- Palestine; Transformational leadership